Oscillatory Dynamics of Prefrontal Cognitive Control. Issue 12 (December 2016) - Helfrich, Randolph F.; Knight, Robert T.
Abstract : The prefrontal cortex (PFC) provides the structural basis for numerous higher cognitive functions. However, it is still largely unknown which mechanisms provide the functional basis for flexible cognitive control of goal-directed behavior. Here, we review recent findings that suggest that the functional architecture of cognition is profoundly rhythmic and propose that the PFC serves as a conductor to orchestrate task-relevant large-scale networks. We highlight several studies that demonstrated that oscillatory dynamics, such as phase resetting, cross-frequency coupling (CFC), and entrainment, support PFC-dependent recruitment of task-relevant regions into coherent functional networks. Importantly, these findings support the notion that distinct spectral signatures reflect different cortical computations supporting effective multiplexing on different temporal channels along the same anatomical pathways. Trends: Prefrontal oscillatory dynamics coordinate cortical and subcortical large-scale networks, providing a functional basis for flexible cognitive control of goal-directed behavior and do not constitute an epiphenomenon of spiking activity. Nonlinear dynamics, including phase resetting, endogenous entrainment, and CFC, support the spatiotemporal organization of functional networks and predict behavior on the single-trial level. Neuronal oscillations provide the temporal reference frame for activity-silent encoding in neuronal assemblies, which complements the view that the neuron is the structural and functional unit of the nervous system. Multiplexing on different temporal channels reflects distinct canonical computations and increases cortical coding capacity. Directionality analyses reveal the timing of information flow along established anatomical pathways.